An objective evaluation of simulated surgical outcomes among surgical trainees using manual small-incision cataract surgery virtual reality simulator - Sankarananthan, R; Prasad, R Senthil; Koshy, Tony Alex; Dharani, Padam; Bacchav, Ashish; Lansingh, Van Charles; Ahiwalay, Chetan; Balagiri, K; Shekhar, Madhu (Indian journal of ophthalmology, 2022)
Purpose: The purpose of this study was to evaluate trainee performance across six modules of a virtual reality (VR) simulator. Methods: A retrospective observational study was conducted on 10 manual small-incision cataract surgery (MSICS) trainees who practiced cataract surgery on an MSICS VR simulator for one month. They were assessed in six major steps which included scleral groove, tunnel dissection, keratome entry, capsulorhexis, nucleus delivery, and intraocular lens (IOL) insertion under a trainer's supervision. The information included in their score metrics was collected, and their overall performance was evaluated. Results: Thirty attempts were evaluated for scleral groove, tunnel dissection, and capsulorhexis and 15 attempts for keratome entry. Candidates had varied results in the dimensional aspects and their rates of complications with a mean satisfactory score of 3.1 ± 4.17, 6.8 ± 5.75, 5.8 ± 7.74, and 1.8 ± 2.57, respectively. Nucleus delivery (n = 5) had more of iris pull and IOL insertion (n = 5) had more of lost IOL as complications but both had a higher satisfactory outcome. Conclusion: A VR simulator is a useful tool for training surgeons before their entry into live surgery. It is an effective method for evaluating objectively the structural characteristics of each phase in MSICS and their associated complications, helping them anticipate it earlier during live surgery by giving them a near real world experience.